The relationship of health beliefs on the stage of mammography behavior adoption amongst women in Kuantan, Pahang - Hanis Aisyah Ramli (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Introduction: Breast cancer (BC) awareness is relatively poor among Malaysian women indicated by the presence of BC at a late stage and the low rate of mammography screening. Only a few theoretically based studies have been conducted on Malaysian women's participation in mammography. However, no study found in Malaysia concurrently used the health belief model (HBM) and stages of change model (SoC) to explain breast cancer screening behavior such as mammography. Further very few studies had been carried out especially on woman living in the east coast of West Malaysia. Therefore, this study aims to use HBM and SoC to determine the relationship between health beliefs on the behavioral adoption of mammography amongst women in Kuantan, Pahang. Methodology: Five hundred and twenty women were randomly selected to complete the survey. Data was analyzed using multinomial logistic regression (MLR) to ascertain the multivariate relationship between health beliefs and stages of mammography behavioral adoption. Results: The chi-square test reflected that a significant difference existed between socio-demographic factors (age, marital status and family income) and the stages of mammography behavioral adoption. The MLR test also indicated that a significant difference existed between health beliefs (perceived susceptibility, severity, barriers, motivator factors and self-efficacy) and the stages of mammography behavioral adoption. Conclusion: Women aged 41 to 55 years and married were found to be possibly conscious of their risk of developing breast cancer. This attribute together with spousal support manifested in them showing positive attitude towards regular mammography screening. Women who have high health belief were most likely to engage in mammography screening as they perceived breast cancer as a threat to their well-being. The data obtained from this study would aid in enhancing educational and interventional programs in promoting awareness and the importance of early breast cancer detection such as adoption of mammography screening. Keywords: Breast cancer, mammography, health behavior, health belief model, stage of change model